Klinički tok infekcije koksakivirusom B (1-6) - Pavic, Sladjana M; Antic, Marija S; Sparic, Radmila M; Pavic, Aleksandra M (PONS - medicinski časopis, 2020)
Introduction: Coxsackie B viral infections are the usual infections of children and adults. Clinical manifestations include fever, aseptic meningitis,  pleurodinia, myocarditis, gastroenterocolitis, maculous exanthem. The clinical course of the infection is influenced by the characteristics of the host, as well as the virus serotype. The pathogenesis of the virus is explained by the immune mediated mechanism and the direct cytotoxic effect of the virus.         Methods: Retrospectively analyzed  virus serotype, clinical and biochemical date in patients with Coxsackie B viral infection. Autoantibodies were found in patients who had an unclear febrile status for more than 6 months.Results: We examined  a total of 378 patients with Coxsackie B viral infection, (302 women, 76 men),  age 19 to 79 years. The dominant symptoms were weakness, elevated body temperature, fatigue and muscle aches. In 55%  the clinical course was unclear febrile state, in 13% myalgia and/pleurodnia,  after 9% acute gastroenterocolitis and acute myocarditis/pericarditis,  4% a septic meningitis and other respiratory disease, 3% acute pancreatitis and 1% diabetes mellitus. Autoantibodies were detected in 69% of patients with unclear febrile state. Antinuclear antibodies were most common, in 67%. In 36% of patients with antinuclear antibodies was detected serotyp B2, in 14% serotyp  B4.Conclusion: The most common clinical form of Coxsackie B viral infection is an unclear febrile state caused by a B2 serotype of the virus. In most of these patients, an elevated titre of antinuclear antibodies can be detected.